Menstimulasi Fisikmotorik Anak Melalui Permainan Memindahkan Bola Di Tk Bunga Delima - SOFI, DIVA ALFIANDRA (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2023)
Playing is one way for chlidren to learn and improve their abilities. Through playing, it makes children physically and psychologically healthy, helps the growth and development of children, especialy gross motor skills. The purpose of this study was to determine the effectiveness of relay games as an activity that uses physical motor skills to improve gross motor skills of children aged 5-6 years. This relay game has 4 playing activities in which there are activities that contain gross motoric elements. This study used a quasi-experimental method with one group pretest-posttest design, and involved 15 children in one kindergarten in Kabupaten MALANG . The results of this study indicate that there is an effect of the use of relay games on gross motor skills of children aged 5-6 years. This relay game activity can also be reference of learning activities in improving children’s gross motor skills at school and outside of school.